2012
DOI: 10.3164/jcbn.11-69
|View full text |Cite
|
Sign up to set email alerts
|

Aegle marmelos fruit extract attenuates isoproterenol-induced oxidative stress in rats

Abstract: Myocardial infarction is a major public health concern and the leading cause of death throughout the world. The present study investigates the ability of Aegle marmelos fruit extract to prevent pathological changes and oxidative stress after isoproterenol induced myocardial infarction in rats. In vitro studies showed that Aegle marmelos fruit extract possesses antioxidant activity. Administration of isoproterenol (85 mg/kg body weight) to rats resulted in significantly elevated plasma transaminases, lactate de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The search for an effective medicine to treat cardiovascular disorders without any side effects has lead to the use of traditional plant based medicine. The indigenous plants such as Aegle marmelos (Krushna et al, 2011), Inula racemosa (Ojha et al, 2011), Punica granatum (Mohan et al, 2010), Myristica fragrans (Kareem et al, 2009), Moringa oleifera (Nandave et al, 2009) and Embelia ribes Burm (Bhandari et al, 2008) have been proved for their cardioprotective activity against ISO-induced MI in rats.…”
Section: Introductionmentioning
confidence: 99%
“…The search for an effective medicine to treat cardiovascular disorders without any side effects has lead to the use of traditional plant based medicine. The indigenous plants such as Aegle marmelos (Krushna et al, 2011), Inula racemosa (Ojha et al, 2011), Punica granatum (Mohan et al, 2010), Myristica fragrans (Kareem et al, 2009), Moringa oleifera (Nandave et al, 2009) and Embelia ribes Burm (Bhandari et al, 2008) have been proved for their cardioprotective activity against ISO-induced MI in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Herbal drugs are widely used, even when their biologically active compounds are unknown, due to their effectiveness, minimal side effects in clinical experience and relatively lower costs (Krushna et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Reports revealed that compounds in their natural formulations are more active than isolated form. (9) …”
Section: Introductionmentioning
confidence: 99%